2005
DOI: 10.1002/ch.8
|View full text |Cite
|
Sign up to set email alerts
|

The ‘hidden observer’ and ideomotor responding: a real‐simulator comparison

Abstract: Subjective reports of the amount of effort required to complete an ideomotor (i.e. arm suspension) task were contrasted across baseline, hypnosis, hidden observer and postsession trials among N = 124 participants who had previously scored in the high or low range on a standardized measure of hypnotizability. Low hypnotizable participants received simulation instructions prior to the experiment. Three different instructions were administered during the hidden observer trial. Participants were told that their hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Accordingly, participants experience diminished behavioral control and respond automatically to suggested events. Hilgard's interpretation of the hidden observer stirred substantial controversy, as studies revealed that the nature of the hidden observer (e.g., reporting more vs. less pain) depended on the suggestions or cues inherent in the communications that elicited the seeming personality dissociation (see Green, Page, et al, 2005;Kirsch & Lynn, 1998). Regardless of the explanation for the hidden observer, the phenomenon highlights the ability of suggestion to facilitate a different and potentially more therapeutic perspective on one's experiences and actions (see Lynn et al, 1994).…”
Section: Neodissociation and Cold Control Theorymentioning
confidence: 99%
“…Accordingly, participants experience diminished behavioral control and respond automatically to suggested events. Hilgard's interpretation of the hidden observer stirred substantial controversy, as studies revealed that the nature of the hidden observer (e.g., reporting more vs. less pain) depended on the suggestions or cues inherent in the communications that elicited the seeming personality dissociation (see Green, Page, et al, 2005;Kirsch & Lynn, 1998). Regardless of the explanation for the hidden observer, the phenomenon highlights the ability of suggestion to facilitate a different and potentially more therapeutic perspective on one's experiences and actions (see Lynn et al, 1994).…”
Section: Neodissociation and Cold Control Theorymentioning
confidence: 99%